Reduction of magnetizing inrush current in a delta connected transformer - Basu, K. P.; Asghar, Ali (2008)
Magnetizing inrush current in power transformer creates severe power quality problems. Energization of the transformer from the delta side of a delta-star transformer does not allow the control of neutral resistor at the time of switching the supply for reducing the inrush current. Controlled switching at peak value of the voltage may reduce inrush current in one winding of the transformer, but the line currents are not reduced. Delayed and controlled energization of the third phase may reduce inrush winding currents in two windings and only one line current is reduced, but the inrush currents in the other two lines become very high [11].